The Influence of Early Marriage History on Stunting Risk: A Systematic Literature Review - Ade Fadly H Masse; Ella Nurlaella Hadi; Mufti As Siddiq M. Irzal; Rezki Nurfatmi (Universitas Pahlawan Tuanku Tambusai, 2025)
Stunting, a chronic growth condition characterized by a height-for-age Z-score below -2 SD of the WHO median, poses significant health, developmental and cognitive challenges. This systematic literature review investigates the relationship between early marriage and the prevalence of stunting, emphasizing its impact on intergenerational malnutrition. Using databases such as ProQuest, Scopus, PubMed and Google Scholar, the study screened 6,679 articles and narrowed them down to 11 high-quality studies based on PRISMA guidelines. Findings showed that children born to teenage mothers face a higher risk of stunting due to lack of nutrition knowledge, limited access to health services and socioeconomic constraints. Early marriage is significantly correlated with high-risk fertility behaviors, including short birth spacing and high parity, which exacerbate stunting rates. In addition, cultural norms that encourage early marriage further exacerbate these challenges. The study highlights the need for multidimensional interventions that focus on delaying marriage and childbirth, improving maternal education, increasing access to healthcare, and empowering women through community- based programs. These strategies aim to break the intergenerational cycle of malnutrition, thereby advancing sustainable development goals and improving children's well-being in the long term.